A case of mediastinal lipoma extending to the neck - IKEJIRI, Koji; TANAKA, Yasutaka; MASUDA, Tomoya; YOSHINAGA, Takashi; URYU, Hideoki; NAKASHIMA, Torahiko (jibi to rinsho, 2021)
We experienced a case involving a 67-year-old man with one of the largest cervicomediastinal lipomas reported in Japan. The lesion extended from the tracheal bifurcation to the left upper cervical region. Radical resection was achieved by cervical and thoracic approaches in several departments. No postoperative complications were noted. A preoperative examination did not rule out the possibility of malignancy; thus, in order to achieve complete resection, the approach should be discussed with multiple departments (otolaryngology, head and neck surgery, esophageal surgery, and respiratory surgery) before the operation.